OGG1 protects mouse spermatogonial stem cells from reactive oxygen species in culture. Issue 3 (30th November 2020) - Mori, Yoshifumi; Ogonuki, Narumi; Hasegawa, Ayumi; Kanatsu-Shinohara, Mito; Ogura, Atsuo; Wang, Yufeng; McCarrey, John R; Shinohara, Takashi
Abstract: Although reactive oxygen species (ROS) are required for spermatogonial stem cell (SSC) self-renewal, they induce DNA damage and are harmful to SSCs. However, little is known about how SSCs protect their genome during self-renewal. Here, we report that Ogg1 is essential for SSC protection against ROS. While cultured SSCs exhibited homologous recombination-based DNA double-strand break repair at levels comparable with those in pluripotent stem cells, they were significantly more resistant to hydrogen peroxide than pluripotent stem cells or mouse embryonic fibroblasts, suggesting that they exhibit high levels of base excision repair (BER) activity. Consistent with this observation, cultured SSCs showed significantly lower levels of point mutations than somatic cells, and showed strong expression of BER-related genes. Functional screening revealed that Ogg1 depletion significantly impairs survival of cultured SSCs upon hydrogen peroxide exposure. Thus, our results suggest increased expression of BER-related genes, including Ogg1, protects SSCs from ROS-induced damage. Abstract : OGG1 suppresses ROS-induced damages in spermatogonial stem cells.